2017
DOI: 10.1111/psyp.12863
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the error‐related negativity across groups: The impact of error‐ and trial‐number differences

Abstract: The error-related negativity (ERN or Ne) is increasingly being investigated as a marker discriminating interindividual factors and moves toward a surrogate marker for disorders or interventions. Although reproducibility and validity of neuroscientific and psychological research has been criticized, clear data on how different quantification methods of the ERN and their relation to available trial numbers affect within- and across-participant studies is sparse. Within a large sample of 863 healthy human partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 40 publications
5
75
0
1
Order By: Relevance
“…That is, for the ERN we examined the likelihood of finding a statistically significant amplitude difference between error trials and correct trials; for the LRP, we examined the likelihood of finding a statistically significant amplitude difference between the hemispheres contralateral versus ipsilateral to the response hand. Consistent with previous work (Fischer et al, 2017;Larson et al, 2010;Olvet & Hajcak, 2009;Pontifex et al, 2010;Steele et al, 2016), the ERN proved to be a robust effect that was reliably observed even when relatively few trials were included in the average (see Figure 6a). In addition, the internal reliability of the ERN reached the "high" range (0.7-0.9) with only 8 error trials, which also replicates prior results (Olvet & Hajcak, 2009).…”
Section: Probability Of Obtaining a Statistically Significant Erp Csupporting
confidence: 90%
See 3 more Smart Citations
“…That is, for the ERN we examined the likelihood of finding a statistically significant amplitude difference between error trials and correct trials; for the LRP, we examined the likelihood of finding a statistically significant amplitude difference between the hemispheres contralateral versus ipsilateral to the response hand. Consistent with previous work (Fischer et al, 2017;Larson et al, 2010;Olvet & Hajcak, 2009;Pontifex et al, 2010;Steele et al, 2016), the ERN proved to be a robust effect that was reliably observed even when relatively few trials were included in the average (see Figure 6a). In addition, the internal reliability of the ERN reached the "high" range (0.7-0.9) with only 8 error trials, which also replicates prior results (Olvet & Hajcak, 2009).…”
Section: Probability Of Obtaining a Statistically Significant Erp Csupporting
confidence: 90%
“…However, as noted by Gehring, Liu, Orr, and Carp (2012, p. 278), "this does not speak to the ability of standard analyses to find between-condition or betweengroup differences." This point has also been made by a recent study, in which the ability to detect a between-groups difference on the ERN was examined as a function of the number of trials included in the ERP average and the error rate across groups (Duncan et al, 2009;Fischer et al, 2017). The study by Fischer et al offered some initial evidence that specific recommendations that are based on tests of ERP stability may not be appropriate as guidelines for detecting differences between groups.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Psychiatric symptoms and transdiagnostic dimensions. We tested if ERN amplitudes were associated to the self-reported symptom scores including error rate (β = 0.40, SE = 0.20, p < 0.04) as a control co-variate, which previously have been shown to influence ERN amplitudes (Fischer et al, 2017). In contrast to our hypothesis, none of the psychiatric questionnaires showed a significant relationship to ERN amplitude (all p > 0.13, where p < 0.005 is the Bonferroni corrected significance threshold) ( Figure 2 and Table 1).…”
Section: Resultsmentioning
confidence: 99%